Пошаговое объяснение:
ответ: x³ + 1/x³ = 322 .
x + 1/x = 7
x³ + 1/x³ = ?
( x + 1/x )³ = x³ + 3x² * 1/x + 3x *( 1/x) ² + ( 1/x )³ = x³ + 3x + 3 * 1/x + 1 /x³ =
= ( x³ + 1/x³ ) + 3 ( x + 1/x ) ;
x³ + 1/x³ = ( x + 1/x )³ - 3( x + 1/x ) = 7³ - 3 * 7 = 343 - 21 = 322 .
Пошаговое объяснение:
ответ: x³ + 1/x³ = 322 .
Пошаговое объяснение:
x + 1/x = 7
x³ + 1/x³ = ?
( x + 1/x )³ = x³ + 3x² * 1/x + 3x *( 1/x) ² + ( 1/x )³ = x³ + 3x + 3 * 1/x + 1 /x³ =
= ( x³ + 1/x³ ) + 3 ( x + 1/x ) ;
x³ + 1/x³ = ( x + 1/x )³ - 3( x + 1/x ) = 7³ - 3 * 7 = 343 - 21 = 322 .